1994
DOI: 10.1159/000112109
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Gliosis as a Consequence of Interleukin-6 Expression in the Brain: Studies in Transgenic Mice

Abstract: Gliosis is a characteristic pathologic state in many CNS disorders. Cytokines are considered to be effectors of gliosis. In order to explore the role of IL-6 in gliosis, the temporal and spatial expression of the IL-6 gene and its consequent effects on the brain were studied in a GFAP-IL6 transgenic mouse model. In GFAP-IL6 mice, IL-6 transgene expression was detectable in the brain at 1 week postnatally and increased to maximal levels by 3 months of age before declining at 8 and 12 months. Enhanced glial fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
134
2
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(158 citation statements)
references
References 52 publications
16
134
2
3
Order By: Relevance
“…Degeneration of severed axon tracts appears to lead to gliosis, even in regions remote from the site of trauma in the brain or spinal cord (Barrett et al, 1981;Fitch and Silver, 1997a;Massey, et al, 2006;Murray et al, 1990;Steward and Trimmer, 1997). Cytokines or other molecules that may trigger gliosis include TNF-alpha (Rostworowski et al, 1997), endothelin-1 (Hama et al, 1997), IL-1 (Giulian and Lachman, 1985), IL-6 (Chiang et al, 1994), thrombin (Nishino et al, 1993), and CNTF (Kahn et al, 1995). Some of these may originate as soluble serum factors, or they can be directly produced by astrocytes, activated microglia, or peripheral macrophages.…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
“…Degeneration of severed axon tracts appears to lead to gliosis, even in regions remote from the site of trauma in the brain or spinal cord (Barrett et al, 1981;Fitch and Silver, 1997a;Massey, et al, 2006;Murray et al, 1990;Steward and Trimmer, 1997). Cytokines or other molecules that may trigger gliosis include TNF-alpha (Rostworowski et al, 1997), endothelin-1 (Hama et al, 1997), IL-1 (Giulian and Lachman, 1985), IL-6 (Chiang et al, 1994), thrombin (Nishino et al, 1993), and CNTF (Kahn et al, 1995). Some of these may originate as soluble serum factors, or they can be directly produced by astrocytes, activated microglia, or peripheral macrophages.…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
“…M88242) was synthesized by RT-PCR using mouse brain RNA as a template and cloned into pGEM-4. Fragments of the RPL32-4A gene (31) and the inducible NO synthase (iNOS) gene (32) were also cloned into pGEM-4. L32 served as an internal loading control.…”
Section: Rnase Protection Assaymentioning
confidence: 99%
“…Such alterations could presumably make an important contribution to the clinicopathological features of many neurological disorders, but the possibility that they are simply the consequence and not the cause must be ruled out experimentally. Results obtained in transgenic mice with astrocyte-targeted expression of cytokines such as IL-6 (5,6,8,12,14,31,52,60), IL-3 (13), IFN-␣ (1), and TNF-␣ (59) have unequivocally demonstrated that an abnormal cytokine production has the potential to cause devastating neurological disorders. Interestingly, each of these cytokines caused a specific repertoire of clinicopathological sequelae that presumably reflect the unique actions of the particular cytokine expressed.…”
Section: Introductionmentioning
confidence: 99%